Educating to regenerate and select. Convergences between the eugenic and educational principles in Brazil - Gualtieri, Regina Cândida Ellero (FCL-UNESP Laboratório Editorial, 2008)
This article discusses convergences between eugenics and the Brazilian pedagogic educational principles in the beginning of the 20th century. The eugenical ideal stated that individual differences were biologically determined and this conception was considered a progressive idea by educators like Fernando de Azevedo (1894-1974) who belonged to the Eugenics Society of Sao Paulo (1918-1919). In this perspective, every individual was entitled to being educated as well as regenerated according to his abilities and this meant that education wouldn’t be treated as a privilege of the social high classes anymore. Such understanding evokes what Michel Foucault named “biopower” – a way to control an entire population for the sake of protecting the “human species” through norms and regulations that qualify and rank individuals, placing men and women according to their “value and usefulness”. Many of these issues remain as a part of the present educational scenario.